A green and sustainable cellulose-based lubricant and its preparation method
By using waste wood to prepare cellulose composite two-dimensional material lubricants, the problems of high cost and insufficient lubricating performance of green lubricants are solved, and low-cost, environmentally friendly and efficient lubricating effects are achieved, and it is suitable for a variety of mechanical equipment.
Patent Information
- Application Number
- CN202310389875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-12
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-04-12
AI Technical Summary
The existing green lubricants have high cost, high technical content, insufficient lubricating performance and limited application scope, making it difficult to find a balance between environmental protection and economic benefits.
Use waste wood as raw material, and through deep eutectic solvent treatment and mechanical crushing, a cellulose composite two-dimensional material lubricant is prepared. The synergistic action of cellulose and two-dimensional materials such as h-BN is used to form an excellent dispersion stability. Water-based lubricants reduce production costs and improve lubricating performance.
It realizes a green lubricant with low cost, environmental protection, wear resistance and stability. It is suitable for a variety of mechanical equipment, extends service life, reduces friction coefficient, and significantly improves the lubricating effect.
Smart Images

Figure CN116396793B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lubricants and relates to green lubricants, and in particular to a green and sustainable cellulose-based lubricant and a preparation method thereof. Background Art
[0002] With the increasing awareness of environmental protection and the demand for sustainable development, the research and development of green lubricants has become an important field. Green lubricants refer to lubricants that reduce pollution to the environment and harm to human health while lubricating, and have good biodegradability and renewability. In the past, traditional lubricants usually contained petrochemicals and toxic and harmful substances, which have adverse effects on the environment and human health. For example, petrochemicals will produce a large amount of carbon dioxide emissions, exacerbating global climate change; while toxic and harmful substances will cause harm to human health, such as carcinogenicity and sensitization. In order to solve these problems, people began to study green lubricants, using natural materials and environmental protection technologies to reduce harm to the environment and human health. With the continuous advancement of technology, more and more green lubricants have been invented, such as water-based lubricants, biodegradable lubricants, etc. These lubricants not only have good lubrication properties, but also have less harm to the environment and human health, and have become an important part of modern industrial production. In general, the background of the invention of green lubricants is the need for environmental protection and sustainable development. With the continuous advancement of green technology, green lubricants will play an increasingly important role in future industrial production.
[0003] Common green lubricants mainly include the following: (1) Water-based lubricants: Water-based lubricants are green lubricants based on water. They use water as a solvent and add a small amount of surfactants and additives. They have excellent lubrication and antioxidant properties, and can also reduce pollution to the environment. (2) Biodegradable lubricants: Biodegradable lubricants are green lubricants based on renewable raw materials. They are made from vegetable oils, animal oils and other biomass. They have good biodegradability and renewability, and can also reduce harm to the environment and human health. (3) Food-grade lubricants: Food-grade lubricants are green lubricants specifically used in food processing. They are made from food-grade raw materials, do not contain toxic and harmful substances, are harmless to human health, and can improve the efficiency and quality of food processing. (4) Supercritical lubricants: Supercritical lubricants are green lubricants that use supercritical fluids as lubricants. Supercritical fluids have high solubility and permeability, can improve the lubrication effect, and also have good environmental performance. In general, green lubricants are a type of lubricant with good environmental performance and sustainable development. With the continuous development of technology, more and more green lubricants have been invented, making greater contributions to industrial production and environmental protection. Although green lubricants have many advantages over traditional lubricants, they also have some disadvantages, mainly including the following: (1) High cost: The manufacturing cost of green lubricants is relatively high because they usually require the use of more expensive raw materials and production processes. (2) High technical content: The production of green lubricants requires higher technical content than traditional lubricants, which also increases the difficulty and cost of production. (3) There may be problems with insufficient lubrication performance: The lubrication performance of some green lubricants may not be as good as that of traditional lubricants, which may have a certain impact on the operation and life of mechanical equipment. (4) There may be problems with limited scope of application: Different types of green lubricants are suitable for different mechanical equipment and processes, so there may be problems with limited scope of application. In general, green lubricants have many advantages in environmental protection and sustainable development, but it is also necessary to select suitable products according to specific circumstances in actual applications to balance environmental protection and economic benefits. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to improve a green and sustainable cellulose-based lubricant and a preparation method thereof, to prepare a green and sustainable cellulose-based lubricant with high wear resistance, excellent stability and sustainability, which is low-cost, green, environmentally friendly and pollution-free.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a green and sustainable cellulose-based lubricant comprises the following steps:
[0007] Step 1, treating the waste wood raw material with a deep eutectic solvent (DES) formed by mixing choline chloride and dihydrate oxalic acid at a mass ratio of (1:1) at 100° C., stirring at 100-120° C. for 3-5 hours to completely dissolve the wood powder, then quickly diluting with water and filtering and washing, dispersing the filter residue in water to obtain a primary dispersion and mechanically crushing the dispersion;
[0008] The volume ratio of DES, the mass of wood raw materials and the volume ratio of water in the primary dispersion is 200 mL: (2.5-3.5 g): (200-400 mL);
[0009] Step 2: adding sodium chlorite and acetic acid to the primary dispersion and stirring at 100-120° C. for 3-5 hours, filtering and washing the mixture after the reaction is completed, dispersing the filter residue in water to obtain a secondary dispersion, and mechanically crushing the mixture again to obtain a cellulose fibril dispersion;
[0010] The volume ratio of the primary dispersion, the mass of sodium chlorite, the volume of acetic acid and the volume of the secondary dispersion is 200 mL: (4.0-6.0 g): (2.0-3.0 mL): (150-200 mL);
[0011] Step 3: Mixing ethylene glycol with a cellulose fibril dispersion at a volume ratio of (1:1) to obtain a tertiary dispersion, and adding the two-dimensional material into the tertiary dispersion for ball milling to obtain a cellulose fibril composite two-dimensional material type lubricant;
[0012] The volume ratio of the tertiary dispersion to the mass ratio of the two-dimensional material is 100 mL: (0.30-0.50 g).
[0013] The present invention also has the following technical features:
[0014] Preferably, the waste wood raw material in step 1 comprises any one or more mixtures of processed waste wood powder, cellulose crude fiber, corn straw, switchgrass or waste secondary wood materials.
[0015] Preferably, the mechanical crushing treatment time in step 1 and step 2 is 60 to 120 minutes.
[0016] Preferably, the two-dimensional material described in step three includes any one of hexagonal boron nitride, flake graphite, graphite fluoride, molybdenum disulfide or mica.
[0017] Preferably, the ball milling treatment in step three is performed at 400-500 rpm for 12-16 hours.
[0018] The present invention also protects a green and sustainable cellulose-based lubricant prepared by the method as described above.
[0019] Compared with the prior art, the present invention has the following technical effects:
[0020] The present invention uses waste wood as raw material to extract micro-nano cellulose fibrils, and then further uses cellulose to assist in in-situ exfoliation of two-dimensional materials in a water-ethylene glycol dispersion phase. The exfoliated two-dimensional materials are in-situ loaded on the surface of the cellulose fibrils to directly form a water-based lubricant with excellent dispersion stability.
[0021] The cellulose composite two-dimensional material type water-based lubricant prepared by the present invention has excellent lubricity and friction reduction and anti-wear effects. Since the esterified cellulose surface contains a large number of esterified functional groups, it can form hydrogen bonds with a large number of hydroxyl functional groups contained on its surface, so that the esterified cellulose has excellent dispersion stability in the aqueous dispersion system. This hydrogen bond network can interact with the functional groups on the surface of the two-dimensional material (represented by h-BN) to assist the in-situ stripping of the two-dimensional material. At the same time, the cellulose network has a certain buffering effect on the external shear impact force, which can maintain the integrity of the crystal structure of the stripped two-dimensional material to a great extent; the in-situ stripped h-BN can be loaded on the surface of micro-nano cellulose to form a NC@h-BN dispersion with excellent dispersion stability. Based on the synergistic effect of cellulose's anti-wear and h-BN's self-lubricating, the cellulose-based lubricant has good lubrication performance;
[0022] The raw material adopted in the present invention is waste wood. As a typical green natural biomass material, the preparation process does not require the use of any toxic solvents or drugs, and has the advantages of wide sources, large reserves, and green environmental protection; the obtained cellulose nanofibril composite two-dimensional material lubricant is a green lubricant using natural biomass as raw material, does not contain any toxic and harmful substances, has no pollution to the environment, and meets environmental protection requirements; the green lubricant prepared by the present invention has good processing performance, can be compounded with a variety of two-dimensional materials, and prepared into products of various specifications, and has wide applicability; the nanocellulose-based lubricant prepared by the present invention has excellent stability, high temperature resistance and sustainability, can exist stably in a high temperature environment, is not easy to decompose and oxidize, and extends the service life of the material; in addition, the preparation method of the cellulose composite two-dimensional material lubricant prepared by the present invention is simple, low cost, high production efficiency, and has good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a real photo of the cellulose composite two-dimensional material lubricant (NC@h-BN) prepared in Example 1;
[0024] Figure 2 is the FTIR graph of the cellulose composite two-dimensional material lubricant (NC@h-BN) prepared in Example 1;
[0025] Figure 3 is the XRD spectrum of the cellulose composite two-dimensional material lubricant (NC@h-BN) prepared in Example 1;
[0026] Figure 4 is an optical microscopic morphology image of the cellulose composite two-dimensional material lubricant (NC@h-BN) prepared in Example 1;
[0027] Figure 5 is a friction coefficient curve of the cellulose composite two-dimensional material lubricant (NC@h-BN) prepared in Example 1;
[0028] Figure 6 It is a friction coefficient curve of various types of cellulose composite two-dimensional material lubricants (NC@G, NC@FG, NC@MoS2, NC@MIC) prepared in Examples 4 to 7. DETAILED DESCRIPTION
[0029] The specific contents of the present invention are further explained in detail below in conjunction with embodiments.
[0030] Example 1
[0031] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0032] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 2.5 g corn straw powder to 200 mL of DES, continue stirring at 100°C for 3 hours, wait for the corn straw powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 3 times, and disperse the filter residue in 200 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 60 minutes;
[0033] Step 2: Add 4.0 g of sodium chlorite and 2.0 mL of acetic acid to the primary dispersion and heat and stir at 100° C. for 3 hours. After the reaction is completed, filter and wash the mixture with water for 3 to 5 times, and disperse the residue in 150 mL of distilled water to obtain a secondary dispersion, which is mechanically crushed again for 60 minutes to obtain a cellulose fibril dispersion;
[0034] Step 3: Mix 50 mL of ethylene glycol with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and add 0.30 g of hexagonal boron nitride (h-BN) to the tertiary dispersion and ball mill at 400 rpm for 16 hours to obtain a cellulose fibril composite h-BN type lubricant, marked as NC@h-BN.
[0035] Please refer to Figure 1 The figure shows the dispersion stability of the NC@h-BN lubricant prepared in Example 1. Figure 1 It can be clearly seen that it exhibits excellent stability. Even after 30 days of storage, no precipitation or stratification occurs. Since the esterified cellulose surface contains a large number of esterified functional groups, it can form hydrogen bonds with the hydroxyl functional groups on its surface, making the esterified cellulose have excellent dispersion stability in the aqueous dispersion system. This hydrogen bond network can interact with the functional groups on the surface of the two-dimensional material to assist the in-situ exfoliation of the two-dimensional material. At the same time, the cellulose network has a certain buffering effect on the external shear impact force, which can maintain the integrity of the crystal structure of the exfoliated two-dimensional material to a great extent. The in-situ exfoliated h-BN can be loaded on the surface of micro-nano cellulose to form a NC@h-BN dispersion with excellent dispersion stability.
[0036] Please refer to Figure 2 The figure shows the infrared spectrum of the NC@h-BN lubricant prepared in Example 1. Figure 2 It can be clearly seen that after cellulose and h-BN are composited, the peak positions of the two are basically the same, and the corresponding functional group positions are basically the same. Taking the infrared spectrum of h-BN as a reference, the infrared spectrum of NC@h-BN has stretching vibration peaks corresponding to the BO and BNB groups of h-BN at 1380 and 810 cm-1. The peak at 1730 cm-1 represents the carbonyl esterification functional group on the surface of cellulose fibrils. These evidences show that cellulose and h-BN are successfully composited.
[0037] Please refer to Figure 3 The figure shows the XRD spectrum of the NC@h-BN lubricant prepared in Example 1. The spectrum of NC@h-BN shows obvious peaks corresponding to cellulose nanofibers, which is mainly attributed to the continuous hydration and protonation of DES, as well as the vibration and destruction during the mechanical crushing process, which eliminate most of the amorphous cellulose and increase its crystallinity. At the same time, the exfoliation of cellulose fibrils on h-BN significantly enhances its crystallinity, which is shown in the XRD spectrum as a higher and sharper XRD peak corresponding to h-BN.
[0038] Please refer to Figure 4 As shown, it is a microscopic light microscope photograph of the microstructure of the NC@h-BN lubricant prepared in Example 1. The cellulose micro-nano fibrils are entangled with each other to form an interlaced network structure, and the h-BN peeled off during the ball milling process is in situ loaded on the surface of the cellulose network to form the NC@h-BN nano-lubricating additive.
[0039] Please refer to Figure 5The figure shows the friction coefficient curve of the NC@h-BN lubricant prepared in Example 2 on the surface of engineering steel. Based on the anti-wear properties of cellulose micro-nano fibrils and the interlayer slip effect between h-BN nanosheets, it has excellent lubrication properties. Under the condition of 5N / 200rpm, the friction coefficient of the engineering steel surface is reduced to 0.06. Compared with traditional water-based lubricants, the lubrication effect of the NC@h-BN lubricant is significantly improved. Its excellent lubrication effect is mainly based on the following two points: (1) Cellulose is a high molecular weight polysaccharide that can absorb water and swell in water to form a colloidal solution. At the same time, the surface of cellulose fibril molecules also has a certain charge, so it can interact electrostatically with other charged molecules or ions, thereby forming a protective lubricating film on the surface. In addition, there are certain intermolecular forces between cellulose molecular chains, so they can form a layer of lubricant-like substance on the surface to reduce friction and wear. (2) The interlayer bonding force of h-BN is weaker than the bonding force between adjacent BN atoms within the layer. During the friction process, the layers have a lower shear strength, which makes it easy for adjacent layers to slip relative to each other, showing a better lubrication effect. Based on the synergistic effect of cellulose fibrils and h-BN, the friction coefficient of NC@h-BN lubricant on the surface of engineering steel is significantly reduced.
[0040] Example 2
[0041] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0042] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 3.5 g of poplar wood powder to 200 mL of DES, continue stirring at 100°C for 5 hours, wait for the poplar wood powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 400 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 120 minutes;
[0043] Step 2: 200 mL of the primary dispersion was added with 6.0 g of sodium chlorite and 3.0 mL of acetic acid and heated and stirred at 100° C. for 5 hours. After the reaction was completed, the mixed solution was filtered and washed with water for 45 times, and the filter residue was dispersed in 200 mL of distilled water to obtain a secondary dispersion, which was mechanically crushed again for 120 min to obtain a cellulose fibril dispersion;
[0044] Step 3: Mix 50 mL of ethylene glycol with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and add 0.50 g of hexagonal boron nitride (h-BN) to the tertiary dispersion and ball mill at 500 rpm for 12 hours to obtain a cellulose fibril composite h-BN type lubricant, marked as NC@h-BN.
[0045] Example 3
[0046] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0047] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 3.0 g of poplar powder to 200 mL of DES, continue stirring at 120° C. for 4 hours, wait for the poplar powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 300 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 80 minutes;
[0048] Step 2: Take 200 mL of the primary dispersion, add 5.0 g of sodium chlorite and 2.5 mL of acetic acid, and heat and stir at 120° C. for 3 hours. After the reaction is completed, filter and wash the mixture 5 times, and disperse the residue in 200 mL of distilled water to obtain a secondary dispersion, and perform mechanical crushing again for 80 minutes to obtain a cellulose fibril dispersion;
[0049] Step 3: Mix 50 mL of ethylene glycol with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and add 0.40 g of hexagonal boron nitride (h-BN) to the tertiary dispersion and ball mill at 450 rpm for 14 hours to obtain a cellulose fibril composite h-BN type lubricant, marked as NC@h-BN.
[0050] Example 4
[0051] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0052] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 2.5 g of willow powder to 200 mL of DES, continue stirring at 110°C for 3 hours, wait for the willow powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 300 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 80 minutes;
[0053] Step 2: Take 200 mL of the primary dispersion, add 4.0 g of sodium chlorite and 2.0 mL of acetic acid, and heat and stir at 110° C. for 4 hours. After the reaction is completed, filter and wash the mixture 5 times, and disperse the residue in 180 mL of distilled water to obtain a secondary dispersion, and perform mechanical crushing again for 80 minutes to obtain a cellulose fibril dispersion;
[0054] Step 3: 50 mL of ethylene glycol was mixed with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and 0.40 g of graphite fluoride (FG) was added to the tertiary dispersion and ball milled at 400 rpm for 14 hours to obtain a cellulose fibril composite FG type lubricant, which was marked as NC@FG.
[0055] Example 5
[0056] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0057] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 2.5 g of poplar wood powder to 200 mL of DES, continue stirring at 110° C. for 3 hours, wait for the poplar wood powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 300 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 80 minutes;
[0058] Step 2: Take 200 mL of the primary dispersion, add 4.0 g of sodium chlorite and 2.0 mL of acetic acid, and heat and stir at 110° C. for 4 hours. After the reaction is completed, filter and wash the mixture 5 times, and disperse the residue in 180 mL of distilled water to obtain a secondary dispersion, and perform mechanical crushing again for 80 minutes to obtain a cellulose fibril dispersion;
[0059] Step 3: Mix 50 mL of ethylene glycol with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and add 0.40 g of flake graphite (G) to the tertiary dispersion and ball mill at 500 rpm for 12 hours to obtain a cellulose fibril composite G-type lubricant, marked as NC@G.
[0060] Example 6
[0061] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0062] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 2.5 g of poplar wood powder to 200 mL of DES, continue stirring at 110° C. for 3 hours, wait for the poplar wood powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 300 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 80 minutes;
[0063] Step 2: Take 200 mL of the primary dispersion, add 4.0 g of sodium chlorite and 2.0 mL of acetic acid, and heat and stir at 110° C. for 4 hours. After the reaction is completed, filter and wash the mixture 5 times, and disperse the residue in 180 mL of distilled water to obtain a secondary dispersion, and perform mechanical crushing again for 80 minutes to obtain a cellulose fibril dispersion;
[0064] Step 3: Mix 50 mL of ethylene glycol with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and add 0.40 g of molybdenum disulfide (MoS2) to the tertiary dispersion and ball mill at 400 rpm for 16 hours to obtain a cellulose fibril composite MoS2 type lubricant, marked as NC@MoS2.
[0065] Example 7
[0066] A green and sustainable method for preparing a cellulose-based lubricant, the preparation method comprising the following steps:
[0067] Step 1: Use a deep eutectic solvent (DES) formed by mixing choline chloride and oxalic acid dihydrate in equal amounts, add 2.5 g of poplar wood powder to 200 mL of DES, continue stirring at 110° C. for 3 hours, wait for the poplar wood powder to be completely dissolved, quickly add 200 mL of distilled water to dilute, filter and wash 5 times, and disperse the filter residue in 300 mL of distilled water to obtain a primary dispersion, which is then mechanically crushed for 80 minutes;
[0068] Step 2: Take 200 mL of the primary dispersion, add 4.0 g of sodium chlorite and 2.0 mL of acetic acid, and heat and stir at 110° C. for 4 hours. After the reaction is completed, filter and wash the mixture 5 times, and disperse the residue in 180 mL of distilled water to obtain a secondary dispersion, and perform mechanical crushing again for 80 minutes to obtain a cellulose fibril dispersion;
[0069] Step 3: 50 mL of ethylene glycol was mixed with 50 mL of cellulose dispersion to obtain a tertiary dispersion, and 0.40 g of mica (MIC) was added to the tertiary dispersion and ball milled at 500 rpm for 16 hours to obtain a cellulose fibril composite MIC type lubricant, which was marked as NC@MIC.
[0070] Please refer to Figure 6 The figure shows the friction coefficient curves of NC@G, NC@FG, NC@MoS2, and NC@MIC lubricants prepared in Examples 4 to 7 on the surface of engineering steel. It can be found that these cellulose composite two-dimensional material lubricants have excellent lubrication properties, greatly reducing the friction coefficient between steel friction pairs and reducing friction and wear.
[0071] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be included in the scope of the claims.
Claims
1. A method for preparing a green and sustainable cellulose-based lubricant, characterized in that: The following steps are involved: Step 1, treating the waste wood raw material with a deep eutectic solvent (DES) formed by mixing choline chloride and dihydrate oxalic acid at a mass ratio of (1:1) at 100° C., stirring at 100-120° C. for 3-5 hours to completely dissolve the wood powder, then quickly diluting with water and filtering and washing, dispersing the filter residue in water to obtain a primary dispersion and mechanically crushing the dispersion; The volume ratio of DES, the mass of wood raw materials and the volume ratio of water in the primary dispersion is 200 mL: (2.5-3.5 g): (200-400 mL); Step 2: adding sodium chlorite and acetic acid to the primary dispersion and stirring at 100-120° C. for 3-5 hours, filtering and washing the mixture after the reaction is completed, dispersing the filter residue in water to obtain a secondary dispersion, and mechanically crushing the mixture again to obtain a cellulose fibril dispersion; The volume ratio of the primary dispersion, the mass of sodium chlorite, the volume of acetic acid and the volume of the secondary dispersion is 200 mL: (4.0-6.0 g): (2.0-3.0 mL): (150-200 mL); Step 3: Mixing ethylene glycol with a cellulose fibril dispersion at a volume ratio of (1:1) to obtain a tertiary dispersion, and adding the two-dimensional material into the tertiary dispersion for ball milling to obtain a cellulose fibril composite two-dimensional material type lubricant; The volume ratio of the tertiary dispersion to the mass ratio of the two-dimensional material is 100 mL: (0.30-0.50 g).
2. The method for preparing a green and sustainable cellulose-based lubricant according to claim 1, characterized in that: The waste wood raw materials described in step 1 include any one or more mixtures of processed waste wood powder, cellulose crude fiber, corn straw, switchgrass or waste secondary wood materials.
3. The method for preparing a green and sustainable cellulose-based lubricant according to claim 1, characterized in that: The mechanical crushing treatment time described in step 1 and step 2 is 60 to 120 minutes.
4. The method for preparing a green and sustainable cellulose-based lubricant according to claim 1, characterized in that: The two-dimensional material described in step three includes any one of hexagonal boron nitride, flake graphite, graphite fluoride, molybdenum disulfide or mica.
5. The method for preparing a green and sustainable cellulose-based lubricant according to claim 1, characterized in that: The ball milling treatment described in step 3 is ball milling at 400-500 rpm for 12-16 hours.
6. A green and sustainable cellulose-based lubricant prepared by the method according to any one of claims 1 to 5.